2014
DOI: 10.1302/0301-620x.96b1.30923
|View full text |Cite
|
Sign up to set email alerts
|

Raised levels of metal ions in the blood in patients who have undergone uncemented metal-on-polyethylene Trident–Accolade total hip replacement

Abstract: The issues surrounding raised levels of metal ions in the blood following large head metal-on-metal total hip replacement (THR), such as cobalt and chromium, have been well documented. Despite the national popularity of uncemented metal-on-polyethylene (MoP) THR using a large-diameter femoral head, few papers have reported the levels of metal ions in the blood following this combination. Following an isolated failure of a 44 mm Trident-Accolade uncemented THR associated with severe wear between the femoral hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Increased cobalt ions were seen in a series with the same implants as our cases that used 36 mm diameter heads [21]. Although the significance of this finding is not fully clear, we now suggest that metal ion testing should form part of the investigation protocol of a symptomatic THA.…”
Section: Discussionsupporting
confidence: 62%
“…Increased cobalt ions were seen in a series with the same implants as our cases that used 36 mm diameter heads [21]. Although the significance of this finding is not fully clear, we now suggest that metal ion testing should form part of the investigation protocol of a symptomatic THA.…”
Section: Discussionsupporting
confidence: 62%
“…Several studies on elevated metal ion levels or even catastrophic gross taper failures (GTF) after hip joint replacement highlight one particular stem design with a small V-40 taper made from a less stiff Ti-12Mo-6Zr-2Fe titanium-alloy (TMZF; Accolade I, Stryker, Mahwah, NJ) in combination with head sizes of mostly 36mm and above ( Figure 1) [9][10][11][12][13][14][15][16][17][18]. This proprietary beta titanium alloy was introduced in 2002 based on the potential benefits of more closely mimicking the modulus of elasticity of cortical bone than standard Ti-6Al-4V alloys [19].…”
Section: Introductionmentioning
confidence: 99%
“…65 Additionally, Craig et al reported increased serum metal ion levels in LD MoP hips compared with small diameter from a single manufacturer. 66 Furthermore, the NJR shows higher revision rates for MoP hips ≥36 mm head diameter. 4 Therefore, pseudotumor formation in MoP THRs is perhaps associated with increased bearing diameter size.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to this Balso et al conducted a semiquantitative scoring study on retrieved of MoP THRs and reported the possibility of accelerated fretting damage due to increased femoral head size . Additionally, Craig et al reported increased serum metal ion levels in LD MoP hips compared with small diameter from a single manufacturer . Furthermore, the NJR shows higher revision rates for MoP hips ≥36 mm head diameter .…”
Section: Discussionmentioning
confidence: 99%